1973
DOI: 10.1073/pnas.70.12.3511
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenesis in Implants of Insoluble Bone Gelatin

Abstract: Insoluble bone gelatin with inclusions of insoluble noncollagenous protein produces new bone when implanted in muscle in allogeneic rats. The implanted residue provides the milieu for expression of bone morphogenetic potential of migratory mesencliymal cells. Neutral buffer solutions activate endogenous enzymes that degrade components essential for cell interactions and differentiation of bone. Chloroform-methanol either denatures or extracts constituents responsible for degradation. Insoluble bone gelatin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
6

Year Published

1974
1974
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(86 citation statements)
references
References 25 publications
0
80
0
6
Order By: Relevance
“…This process was known as demineralization, and the obtained tissue is referred as demineralized bone. 22 The proteins were then extracted by incubation of demineralized bone slices in denaturing buffer of 6 M guanidine-HCl and 100 mM Tris (pH 7.4). For comparison, the undemineralized bone slices were also incubated in the same denaturing buffer for extraction of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This process was known as demineralization, and the obtained tissue is referred as demineralized bone. 22 The proteins were then extracted by incubation of demineralized bone slices in denaturing buffer of 6 M guanidine-HCl and 100 mM Tris (pH 7.4). For comparison, the undemineralized bone slices were also incubated in the same denaturing buffer for extraction of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…TGFβ-like BMPs play a broad range of roles in processes that include dorsal/ventral patterning, organogenesis, neural development (Hogan, 1996;Furuta et al, 1997;De Robertis and Kuroda, 2004), and osteogenesis (Urist et al, 1973;Wozney et al, 1988). In particular, signaling gradients of BMP2 and BMP4 in vertebrates, and of the Drosophila orthologue decapentaplegic (DPP), are the major determinants for forming the dorsal-ventral axis in gastrulation (Hogan, 1996).…”
Section: Bmps 2 Andmentioning
confidence: 99%
“…In seminal work, Urist and colleagues demonstrated that protein factor(s) from demineralized bone extracts could induce ectopic bone formation (Urist, 1965;Urist et al, 1973) via a process recapitulating the endochondral bone formation of normal development (Reddi and Huggins, 1972). These factor(s) were designated bone morphogenetic protein (BMP) (Urist et al, 1973), and extensive purification of bone inductive activity from bone extracts led to initial isolation of BMPs 1-7 (Celeste et al, 1990;Wang et al, 1988;Wozney et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP was first postulated by Urist in 1965 [23], and was subsequently extracted chemically from demineralized bone matrix [17,24]. Wozney et al [27] employed recombinant DNA technology to produce the proteins in 1988.…”
Section: Methodsmentioning
confidence: 99%